Land Cover Change Dynamics As an Indicator of Deforestation Rate in Gunung Leuser National Park - Rihady Agus; Rahmawaty Rahmawaty; T. Alief Aththorick; Samsuri Samsuri; Erwin Nyak (International Journal of Science and Environment (IJSE), 2026)
Gunung Leuser National Park (GLNP) is one of the most important conservation areas in Indonesia, serving as a habitat for various rare and protected species such as the Sumatran tiger, elephant, rhinoceros, and orangutan. Nevertheless, this area faces serious threats from deforestation caused by human activities, including illegal logging, agricultural expansion, and infrastructure development. This study aims to analyze the rate of deforestation occurring in GLNP from 2008 to 2023, to examine land cover changes in the park up to 2033, and to assess community attitudes, perceptions, and participation related to deforestation in the GLNP area. The methods employed include multi-temporal satellite image analysis (Landsat 5 and Landsat 8) using supervised classification through Google Earth Engine (GEE) and Geographic Information System (GIS) tools. Data accuracy was evaluated using ground truth validation, along with an assessment of community perceptions and participation regarding land cover changes. The results indicate that during the study period, forest area decreased by approximately 18,822.71 hectares (2.38%), accompanied by an increase in shrubland and other non-forest land covers, indicating gradual land conversion. The dominant factors driving deforestation in GLNP include proximity to roads and settlements. Future deforestation rates were predicted using a Cellular Automata–based spatial modeling approach, which estimates land conversion patterns in the absence of mitigation measures. Deforestation in the GLNP area is closely linked to the role of surrounding communities; the findings reveal that local communities are generally less actively involved and less willing to contribute to conservation efforts in GLNP. This study provides important insights for conservation planning and sustainable land-use policy formulation in Gunung Leuser National Park.